• Revision:Indices and Surds

TSR Wiki > Study Help > Subjects and Revision > Revision Notes > Mathematics > Indices and Surds


Indices are used to describe the general term for ^2 in say  x^2 . There are a few laws to know when manipulating expressions involving indices.

Contents

Laws of Indices

 a^m \times a^n = a^{m+n}

 a^m \div a^n = a^{m-n}

 (a^m)^n = a^{mn}

 a^{\frac{1}{m}} = \sqrt[m]{a}

 a^{-m} = \frac{1}{a^m}

 a^{\frac{m}{n}} = \sqrt[n]a^m

 a^0 = 1

Examples

 \sqrt[5]4^3 = (4^3)^{\frac{1}{5}} = (4^{\frac{3}{5}})

 5^3 \times 5^4 = 5^7

 \frac{5^5}{5^2} = 5^{3}

Surds

Surds are basically an expression involving a root, squared or cubed etc...

There are some basic rules when dealing with surds

 \sqrt{a} + \sqrt{a} = 2\sqrt{a}

 6\sqrt{a} - 2\sqrt{a} = 4\sqrt{a}

 \sqrt{a} \times \sqrt{b} = \sqrt{ab}

 \sqrt{\frac{a}{b}} = \frac{\sqrt a}{\sqrt b}

Also notice the special case

 \sqrt{a} \times \sqrt{a} = a^{\frac{1}{2}} \times a^{\frac{1}{2}} = a

Difference of Two Squares

 x^2 - y^2 = (x + y)(x - y) This is called the difference of two squares

Rationalising Surds

When you have a fraction where both the nominator and denominator are surds, rationalising the surd is the process of getting rid of the surd on the denominator.

To rationalise a surd you multiply top and bottom by fraction that equals one. Take the example shown below

 \frac{1}{\sqrt{2}}

To rationalise this multiply by effectively 1

 \frac{1}{\sqrt2} \times \frac{\sqrt 2}{\sqrt{2}}

Can you see why  \frac{\sqrt2}{\sqrt{2}} was chosen? This is because  \sqrt{2} \times \sqrt{2} = 2 so the denominator becomes surd free.

For a more complex term

 \frac{1+\sqrt{2}}{1 - \sqrt{5}}

First of all, we need to get rid of the surd expression on the bottom, you should remember the difference of two squares formula.

 a^2 - b^2 = (a + b)(a - b)

suppose a = 1 and b =  \sqrt{5}

 1^2 - 5 = (1+\sqrt{5})(1 - \sqrt{5}) = -4

So to get rid of the denominator surd we multiply  \frac{1+\sqrt{2}}{1 - \sqrt{5}} by  \frac{{1+\sqrt{5}}}{1+\sqrt{5}} like so.

 \frac{1+\sqrt{2}}{1 - \sqrt{5}} \times \frac{{1+\sqrt{5}}}{1+\sqrt{5}}

 = \frac{(1+\sqrt{2})(1+\sqrt{5})}{(1-\sqrt{5})(1+\sqrt{5})}

 = \frac{1 + \sqrt{5} + \sqrt{2} + \sqrt{10}}{1^2 - 5}

 = -\frac{1}{4} - \frac{\sqrt5}{4} - \frac{\sqrt2}{4} - \frac{\sqrt10}{4}

In general

  • Fractions in the form  \sqrt{\frac{1}{a}} multiply top and bottom by  \sqrt{a}
  • Fractions in the form  \frac{1}{a + \sqrt{b}} multiply the top and bottom by  a - \sqrt{b}
  • Fractions in the form  \frac{1}{a - \sqrt{b}} multiply the top and bottom by  a + \sqrt{b}
Try Learn together, TSR's study area

30,685
revision notes

31,954
mindmaps

30,623
crosswords

13,673
quizzes

create
a study planner

thousands
of discussions


Today on TSR

Find out who won!

TSR community awards 2015

Poll
Would you be influenced by unis giving flexible offers (so you can miss by a grade)?